1304. Antimicrobial Management of Stenotrophomonas maltophilia Pneumonia: Does TMP-SMX Dose Affect Treatment Failure?. (4th December 2021) - Keck, J Myles; Perkins, Nicholson; Adams, Delaney; Warner, Mia; McCommon, Julanne; Hobbs, Athena L
Abstract: Background: Limited literature exists to guide the appropriate antimicrobial choice, dose, and duration for Stenotrophomonas maltophilia ( S. maltophilia ) pneumonia. Methods: This multi-center, retrospective cohort study was conducted in adults diagnosed with S. maltophilia pneumonia in eight hospitals between March 1, 2014 and August 31, 2020. Patients were enrolled into one of two arms: those treated with TMP-SMX and those treated with alternative antibiotics. The primary outcome was a composite of treatment failure, defined as the need for alternative antibiotics with in vitro activity against S. maltophilia, isolation of S. maltophilia on repeat cultures drawn greater than 72 hours from the index culture, or in-hospital mortality. Other clinical outcomes that were accessed include the TMP-SMX dosing regimen, and 30- and 90-day mortality rates. This study was approved by the local Institutional Review Board (IRB). Results: Overall, 213 patients were included; 100 (46.9%) received TMP-SMX, and 113 (53.0%) received alternative therapy. Though there was no difference in treatment failure between the two groups, more patients in the "alternative" antibiotic group required mechanical ventilation (57% vs. 31%, respectively; p < 0.001) (Table 1). 74% of patients who received TMP-SMX received a "low-dose" regimen, characterized by < 10 mg/kg/day. When evaluating treatment failure based on "high" or "low-dose" TMP-SMX, there was no difference in treatment failure. However, we noted that physicians were more likely to utilize an alternative agent in addition to TMP-SMX (p=0.001) compared to an alternative agent. When removing this confounder from the composite endpoint, high-dose TMP-SMX was associated with significantly less treatment failure compared to low dose 23% vs. 49%, respectively (p=0.023). The average TMP-SMX dose of patients in the "low-dose" group was 5 + 2.2 mg/kg/day vs. 13.9 + 3.5 mg/kg/day in the "high-dose group. Moreover, when serum creatinine was evaluated at baseline, day 3, day 5, and day 7, no increase was seen in patients who received high dose TMP-SMX (Table 1). Table 1: Clinical Outcomes Conclusion: These preliminary results suggest that appropriate dosing of TMP-SMX may be more important for clinical success in patients with S. maltophilia pneumonia than the choice of agent. Disclosures: All Authors : No reported disclosures